Keefektifan Konseling Eklektik untuk Meningkatkan Kapasitas Fungsi Sosial dan Kualitas Hidup pada Pasien Skizofrenia - Rosita, Henny (Jurnal Kedokteran Indonesia, 2011)
Background: Current management of schizophrenia emphasizes on eclectic approach using biopsychosocialtheories. In conjunction with the standard anti-psychotic terapy, the eclectic counselingis thought to enhance clinical outcomes of patients with schizophrenia, by accelerating adaptivecapacity recovery that allows normal function of the patients in the society. This study aimed todetermine the effectiveness of eclectic counseling on the social function capacity and quality of life inpatients with schizophrenia.Methods: A double-blinded randomized controlled trial was conducted at RSJD (Mental Hospital)Surakarta. A sample of 34 patients diagnosed as schizophrenia in remission was selected for the study.Seventeen patients received eclectic counseling while the other 17 patients did not receive counseling.The independent variable under study was eclectic counseling delivered by a psychiatrist to thepatients once a week over 8 weeks . The dependent variables were scores in Social and OccupationalFunctioning Assessment Scale (SOFAS), and Clinical Global Impression for Quality of Life (CGI-QL). Multiplelinear regression analysis was performed to estimate the effect of counseling on SOFAS and CGI-QL,while controlling for baseline SOFAS and CGI-QLResults: The face validity and concurrent validity of the Indonesian version of SOFAS had been validatedagainst the gold standard GAF scale to measure social function capacity in patients with schizophrenia.Patients with eclectic counseling had higher SOFAS score than those without counseling (b=7.13;95%CI 2.19 to 12.06; p=0.006). Patients with eclectic counseling had better wuality of life, i.e. lowerCGI-QL score than those without counseling (b= -1.19; 95%CI -2.12 to -0.26; p=0.014 ).Conclusion: In conjunction with the standard anti-psychotic therapy, eclectic counseling is effective tofurther improve social function capacity and quality of life in patients with schizophrenia.Keywords: eclectic counseling, social function capacity, quality of life, schizophrenia